Women Teachers in the Turbulent Educational World of St. John’s, Newfoundland, 1920-1949 - Whitehead, Kay (Acadiensis)

(untitled) (The Department of History at the University of New Brunswick, 2008)
Abstract This article focuses on the experiences of women teachers in the city of St. John’s between the 1920s and the 1940s. Although their daily work was influenced by many social forces, including those of religion, class, colonialism, and gender, women teachers were positioned as curriculum and pedagogical experts in city schools. They also found spaces to contribute their expertise more broadly to teacher training and education policy-making in Newfoundland during this era.